Ditch-structured microporous layers fabricated by nanosecond-pulse laser ablation for enhancing water transport in polymer electrolyte membrane fuel cells. Issue 2 (4th May 2020) - Lee, Dong-Hyun; Kim, Min Kyung; Guim, Hwanuk; Yuk, Seongmin; Choi, Jaeho; Choi, Sungyu; Doo, Gisu; Lee, Dong Wook; Noh, Jiwhan; Kim, Hee-Tak
Abstract : Ditch-structured microporous layers were fabricated by nanosecond-pulse laser ablation for in-plane water transport improvement with various structural designs. Abstract : Water management becomes a more critical issue as the power performance of polymer electrolyte membrane fuel cells (PEMFC) is progressively improved. Herein, we present a ditch-structured microporous layer (MPL) that can prevent water flooding in PEMFCs. In-plane ditch structures are carved on an MPL using a nanosecond-pulse laser ablation technique while preserving the surface porosity of the MPL. When the direction of the ditches is aligned perpendicular to the flow field direction, the power performance is significantly enhanced due to the facilitated mass transport under the rib area. The i – V polarizations and limiting current analysis suggest that not gas transport but water transport is responsible for the power performance enhancement. Compared with a perforated MPL prepared by the same technique, the ditch-structured MPL is more effective in mitigating water flooding. Diagonal and radial ditches exemplify the efficacy in making complex ditch patterns. The delicate structural engineering of the MPL enabled by laser ablation can offer a novel design platform for advanced fuel cells.